Mesenchymal Cells of the Intestinal Lamina Propria - Powell, D.W. (2011)
The mesenchymal elements of the intestinal lamina propria reviewed here are the myofibroblasts, fibroblasts, mural cells (pericytes) of the vasculature, bone marrow–derived stromal stem cells, smooth muscle of the muscularis mucosae, and smooth muscle surrounding the lymphatic lacteals. These cells share similar marker molecules, origins, and coordinated biological functions previously ascribed solely to subepithelial myofibroblasts. We review the functional anatomy of intestinal mesenchymal cells and describe what is known about their origin in the embryo and their replacement in adults. As part of their putative role in intestinal mucosal morphogenesis, we consider the intestinal stem cell niche. Lastly, we review emerging information about myofibroblasts as nonprofessional immune cells that may be important as an alarm system for the gut and as a participant in peripheral immune tolerance.